Analisis Koordinasi Petugas Apron Movement Control (AMC) dalam Menangani Pergerakan Pesawat Udara di Bandar Udara Mopah Merauke - Nur Cahya Wulandari; Rosiana Ulfa (Jurnal Flight Attendant, 2025)
In an effort to improve flight safety, coordination of Apron Movement Control (AMC) officers is an important factor that must be considered. The main goal is to reduce the number of service delays and achieve maximum targets. This study aims to determine the performance of Apron Movement Control (AMC) officers in handling aircraft movements at Mopah Merauke Airport and to determine what obstacles are faced by Apron Movement Control (AMC) unit officers when handling aircraft movements at Mopah Merauke Airport and how to solve them.This research was conducted at Mopah Merauke Airport with an observation process in the field and data collection was carried out on September 5, 2023–September 30, 2023. This research is a qualitative descriptive study. Data collection was reviewed directly through interviews, observations, and documentation activities at Mopah Merauke Airport.This study provides results that the coordination of AMC officers in handling aircraft movements at Mopah Merauke Airport requires unity of action, effective communication, clear division of labor, and strict discipline. Each of these indicators is interrelated to ensure that apron operations run safely, efficiently, and according to schedule. AMC officers at Mopah Merauke Airport face various obstacles in handling aircraft movements on the apron, ranging from limited infrastructure, extreme weather conditions, ineffective communication and operational disruptions from external parties. To overcome these obstacles, various solutions are needed that involve improving infrastructure and using sophisticated technology, socializing with airport authorities and controlling wild animals.